The effect of the queen bee's age on the spring development and honey production of honey bee colonies (Apis mellifera l.) - Takács, Marianna; Oláh, János (Animal welfare, Ethology and Housing Systems (AWETH), 2020)
In Hungary the price of queen bees have risen significantly in recent years. Presently, the rate of acceptance of queens has declined, due mainly to the appearance of the italian honey bee (Apis mellifera ligustica) in our country. A further problem with queen bees is that in hungarian beekeeping practice, beekeepers replace the two-year-old queens, which is explained by the fact that, as the queen’s age adversely affects the egg production, it also manifests in honey production in the honey bee colonies.The aim of the current study was to determine the effects of age of queen bees on the quantity of brood area and honey production of honeybee colonies. The performance of experimental colonies, which had 1, 2 and 3 year-old queens, were compared. Their brood areas (cm2) and acacia honey yield (kg/colony) were measured. During the examination of spring development of honeybee colonies the data were recorded four times between 8thApril and 22nd May in 2018 (with a transparent plastic grid), and the honey supers were weighted before and after the honey harvest to ascertaine the acacia honey yield for each colony.According to our results colonies which headed by one-year old queen bees had 26.5 % higher honey production than colonies in which the queen bees were older. In practical aspects of our results in the brood area we found that there was a significant difference among all three groups.
Keywords: queen bee; honey production; bee brood